EVALUASI FAKTOR TEKNIS PENENTU KRITERIA DRAINASE BERWAWASAN LINGKUNGAN - Sih Andajani; Dina P.A Hidayat (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2019)
Integrated management of water resources is something that must be done to ensure the sustainability of water resources. Based on Minister of Public Works Regulation No. 10 of 2015, water resources management in Indonesia is based on 5 pillars where one of the pillars is the conservation of waterresources. Conservation of water resources is a basic concept of ecodrain wherein rainwater falling as much as possible will be absorbed into the ground again or known as zero runoff. One of the technical factors thatdetermine environmentally sound drainage criteria is the recharge system. In this research, the influence of the application of bioretension and rain garden will be discussed as one of the absorption systems for runoff hydrographs in an area, in this case the Upper Cisadane Watershed is used as the research location. Based on the results of the study, it was obtained the reduction of peak flood discharge with the application of type I, II, III and IV biorescence to the existing peak flood discharge of 26.89-26.93%, and reduction of peak flood discharge with the application of rain garden of 27.73%.